PENGGALIAN DAN INVENTARISASI 1000 JUDUL NASKAH MELAYU DI BANDA ACEH - Nurdin AR (CMES (Center of Middle Eastern Studies), 2017)
The most Indonesian written manuscripts were written in the Netherlands language. These manuscripts could be accessed by one of the following catalogs: Juynboll Catalogue (1899), Ronkel Catalogues (1909), Riclefs and P. Voorhoeve Catalogue (1977) etc. Unfortunately, the Indonesian researchers have no way to utilize them. According to the international catalogs written in Indonesian and foreign languages, The Malay manuscripts found in Banda Aceh reached about 300 titles. After conducting preliminary research and direct observation to the individual and institutional collectors, it was found that the real numbers of them could reach to a thousand titles of manuscripts that still have separated in various local places. On behalf these facts, the research aims to rescue these manuscripts from a disappearing and extinction by conducting inventory that is predicted to be able to push the Indonesian researchers ahead to discovering their substantial contents that in opinion useful for human life. The output of the research is compiling catalog documents of 1000 titles of Malay manuscripts found in Banda Aceh.The theory and method used in this research are the theory of the codicology and the method of the catalog of manuscripts register. The codicology is subfield studying all of the manuscript’s aspects in details such as the place of storing, the owner of the manuscript, the content of the manuscript, etc. Whereas the catalog of a manuscript register is describing all of systematically manuscript’s physical and objective aspect in details. The results of the research will be proposed to be the main gate for entering later philology works i.e. presenting and interpreting the text that in turn can be positioned as a manual directive in social and national life.